2020
DOI: 10.3389/fonc.2020.01331
|View full text |Cite|
|
Sign up to set email alerts
|

GZ17-6.02 and Doxorubicin Interact to Kill Sarcoma Cells via Autophagy and Death Receptor Signaling

Abstract: GZ17-6.02 (602) is presently under phase I clinical evaluation (NCT03775525). We defined the mechanisms by which it interacted with a standard of care therapeutic doxorubicin to kill sarcoma cells. Doxorubicin and 602 interacted to rapidly activate ATM and c-MET, inactivate mTOR, AKT, and p70 S6K, enhance the expression of Beclin1 and reduce the levels of K-RAS and N-RAS. This was followed later by the drugs interacting to reduce expression of MCL-1, BCL-XL, and HDAC6. Knock down of ATM prevented the drugs alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…We next determined a pathway analysis to determine the mechanisms of cell killing. Prior studies in other cell types have shown GZ17-6.02 killing through mechanisms using the death receptor CD95 and autophagosome formation (10)(11)(12). We also previously demonstrated using other agents that activation of ATM can lead to activation of the AMPK followed by mTOR inactivation, ULK1 activation, ATG13 S318 phosphorylation and autophagosome formation (22).…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…We next determined a pathway analysis to determine the mechanisms of cell killing. Prior studies in other cell types have shown GZ17-6.02 killing through mechanisms using the death receptor CD95 and autophagosome formation (10)(11)(12). We also previously demonstrated using other agents that activation of ATM can lead to activation of the AMPK followed by mTOR inactivation, ULK1 activation, ATG13 S318 phosphorylation and autophagosome formation (22).…”
Section: Resultsmentioning
confidence: 51%
“…Specific multiple independent siRNAs to knock down the expression of CD95, FADD, Beclin1, ATG5 and eIF2a, and scramble control, were purchased from Qiagen (Hilden Germany). Control studies were presented showing on-target specificity of our siRNAs, primary antibodies and our phosphospecific antibodies to detect both total protein levels and phosphorylated levels of proteins (10)(11)(12)(19)(20)(21)(22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that while harmine has anti-proliferative effects in tumor cells, the compound appears to lack any anti-proliferative biologic effects in non-transformed cells. We have previously shown that GZ17-6.02 interacted with 5-fluorouracil (5FU) to kill GI tumor cells, with doxorubicin to kill sarcoma cells and with [trametinib + dabrafenib] to kill cutaneous melanoma cells expressing B-RAF V600E ( 1 , 2 ). Our new studies were performed to determine whether GZ17-6.02 could kill non-small cell lung cancer (NSCLC) cells expressing mutant activated forms of the EGF receptor (ERBB1).…”
Section: Introductionmentioning
confidence: 99%